Reconstructing the spatial and temporal dynamics of Ecuador’s artisanal small-scale fisheries from fishers’ perspective - César R. Peñaherrera-Palma; Nicole S. Chinacalle-Martínez; Wendy Gómez Zamora; S. Pamela Jaramillo-Vallejo; Jean P. López-Macías; Omar Safady-Mendoza; M. Estefanía Bravo-Ormaza (PLoS ONE, 2025)
Despite their crucial role in livelihoods and commercial activities in coastal communities, numerous artisanal fisheries are often underreported and underestimated because of the absence of proper monitoring programs since they started. This lack of data hinders the assessment of the spatial dynamics and status of the resources these fisheries have targeted over time. This is especially concerning, considering the severe overexploitation faced by many coastal resources. Using tools to assess local ecological knowledge, the present study summarizes the perceptions of artisanal fishers regarding spatial and temporal changes in their fishing grounds across nearshore and offshore coastal environments in Ecuador, South America. From April to September 2023, 1,366 fishers from 22 fishing villages were interviewed about the state of their resources and how their fishing grounds and catches changed over the decades of the 1980s, 1990s, 2000s, and 2010s. We employed a semi-quantitative virtual abundance change framework to convert categorical trend values into numerical data and to associate these with the fishing grounds described by each fisher per decade. Almost all fishers interviewed (approximately 99%) indicated that fishing yields have declined significantly, that the number of targeted species has increased, and that their fishing areas have expanded and shifted farther from the coast. Specifically, the overall perceived trends indicate that catches in the 2010s were 30% lower than in the pre-1980s and approximately 59.5% lower than in the 2000s. While there was an important increase in the distance to the port of origin through the decades, the core fishing grounds (where 60–100% of fishers operate) were located near the coast within the first 8 nautical miles. The results of this assessment highlight the importance of collaboration between fishers and scientists in reconstructing the historical dynamics of under-assessed coastal fisheries.